Functional Materials Based on Nanoparticle Modified Polypropylene Fibers - Tchaikovskaya, Olga N.; Bocharnikova, Elena N.; Lysak, Ilya A.; Malinovskaya, Tatiana D.; Lysak, Galina V.; Plotnikova, Inna; Sakipova, Saule E. (Micro and Nanosystems, 2021)
Background: The formation and modification of the surface of polypropylene fibers provide a versatile material for a variety of applications. Objective: This research examines the production of new materials by pneumatic spraying of a polypropylene melt jet, on the surface of which metal and metal oxide nanoparticles are prepared using the sol-gel technique and photoreduction followed by ultra-high frequency processing. We used the obtained materials to remove Bisphenol A in the photoreactor. Methods: Based on an analysis of the obtained values of the numerical characteristics in the spray zone and the physical essence of the criteria under consideration, a mechanism for the destruction of the melt jet from the formation of a fiber-forming system is proposed. Analysis of the degradation of Bisphenol A was carried out by electron spectroscopy and fluorescence. Results: A composite active layer, “polymer – inorganic nanoparticles”, on the surface of polypropylene fibers has been demonstrated to create new photocatalytic materials. Bisphenol A in water was examined as a toxicant. Conclusion: Based on the analysis of the obtained values of the numerical characteristics in the spray zone and the physical essence of the considered criteria, it was found that the pressure drop in the nozzle, the nozzle critical section area, and the rheological properties of the melt are dominating factors in the influence on the morphology and size of the ultra-fine fibers obtained by pneumatic spraying. It was determined that materials based on a polypropylene carrier with the largest diameter of 6.71 μm have the best sorption capacity for Bisphenol A. A decrease in the concentration of bisphenol A in water by more than two times in 30 minutes of UV irradiation in the presence of polypropylene was achieved without additional injection of oxidants.
Keywords: Bisphenol A